2022
DOI: 10.1186/s12905-022-01859-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and recurrence of Corynebacterium kroppenstedtii infection in patients with mastitis

Abstract: Background Few studies have investigated the differences in clinical features of patients with mastitis following Corynebacterium kroppenstedtii infection, and most focused on the bacterial antimicrobial susceptibility, detection methods and therapy. Methodology There were 133 patients with mastitis infected by C. kroppenstedtii between August 2016 and September 2019. C. kroppenstedtii was identified using mass spectrometry. The demographics, clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“… 27 It has been found that GLM abscess formation is associated with N and ESR, and that high levels of N and ESR can promote GLM abscess formation. 9 , 10 , 28 ESR refers to the rate at which erythrocytes settle under certain conditions, which is related to inflammatory factors in the plasma, the number of erythrocytes, fibrin, etc. During abscess formation, an elevated ESR may indirectly reflect the intensity of inflammation in the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 It has been found that GLM abscess formation is associated with N and ESR, and that high levels of N and ESR can promote GLM abscess formation. 9 , 10 , 28 ESR refers to the rate at which erythrocytes settle under certain conditions, which is related to inflammatory factors in the plasma, the number of erythrocytes, fibrin, etc. During abscess formation, an elevated ESR may indirectly reflect the intensity of inflammation in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that there is a series of inflammatory reactions during the formation of GLM abscesses, patients may present with fever and elevated inflammatory markers such as serum white blood cell (WBC), erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) and neutrophil count (N). [9][10][11][12] In addition, the process of abscess formation may also present a pathophysiological state called a "cytokine storm". 11,13 For example, inflammatory cytokines such as interleukin-10 (IL-10) can induce abscess formation through the mitogen-activated protein kinase (MAPK) pathway.…”
Section: Introductionmentioning
confidence: 99%
“… 37 , 38 Corynebacterium kroppenstedtii is considered a challenging pathogen associated with GLM. 39 Zeng 40 reported that the recurrence rate of treatment combining steroids with antibacterial drugs was significantly lower than that of steroids alone. Commonly chosen antimicrobial agents include doxycycline, amoxicillin, ciprofloxacin, and cefuroxime.…”
Section: Discussionmentioning
confidence: 99%
“…These two cases validate the idea that timely anti-infection treatment is effective and necessary for inhibiting Corynebacterium (Wolfrum et al, 2018 ; Yaghan et al, 2020 ). As Corynebacterium abundance decreases, the symptoms will also resolve (Johnstone et al, 2017 ; Zeng et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study was supported by the Beijing Ten Million Talent Plan Project (No. 2019A31), Research and Transformation of Clinical Diagnosis and Treatment Technology in Beijing (Z211100002921020), Gansu Provincial Science and Technology Program Subsidized Projects (21JRIRG303), and Young Doctor Scholar Project (2022).…”
Section: Data Availability Statementmentioning
confidence: 99%